Diagnosis and prevalence of diabetic polyneuropathy: a cross‐sectional study of Danish patients with type 2 diabetes. (9th September 2020) - Gylfadottir, S. S.; Itani, M.; Krøigård, T.; Kristensen, A. G.; Christensen, D. H.; Nicolaisen, S. K.; Karlsson, P.; Callaghan, B. C.; Bennett, D. L.; Andersen, H.; Tankisi, H.; Nielsen, J. S.; et al.
Abstract : Background and purpose: Diabetic polyneuropathy (DPN) is a common complication of diabetes. Using the Toronto criteria for diabetic polyneuropathy and the grading system for neuropathic pain, the performance of neuropathy scales and questionnaires were assessed by comparing them to a clinical gold standard diagnosis of DPN and painful DPN in a cohort of patients with recently diagnosed type 2 diabetes. Methods: A questionnaire on neuropathy and pain was sent to a cohort of 5514 Danish type 2 diabetes patients. A sample of 389 patients underwent a detailed clinical examination and completed neuropathy questionnaires and scales. Results: Of the 389 patients with a median diabetes duration of 5.9 years, 126 had definite DPN (including 53 with painful DPN), 88 had probable DPN and 53 had possible DPN. There were 49 patients with other causes of polyneuropathy, neuropathy symptoms or pain, 10 with subclinical DPN and 63 without DPN. The sensitivity of the Michigan Neuropathy Screening Instrument questionnaire to detect DPN was 25.7% and the specificity 84.6%. The sensitivity of the Toronto Clinical Neuropathy Scoring System, including questionnaire and clinical examination, was 62.9% and the specificity was 74.6%. Conclusions: Diabetic polyneuropathy affects approximately one in five Danish patients with recently diagnosed type 2 diabetes but neuropathic pain is not as common as previously reported. Neuropathy scales with clinical examination perform better compared with questionnaires alone, but better scales are needed for future epidemiological studies.